2nd European Conference on Antennas and Propagation (EuCAP 2007) 2007
DOI: 10.1049/ic.2007.1555
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and ray-tracing simulation of the 60 GHz indoor broadband channel: model accuracy and parameterization

Abstract: In this paper, we examine millimeter wave propagation in an application-oriented indoor environment by means of broadband channel measurements and ray-tracing simulations. Fundamental issues concerning the choice of simulation parameters are discussed. We investigate the accuracy of ray-tracing predictions in the millimeter wave band with regard to wideband analyses. The results indicate that ray-tracing simulations are useful to predict channel measures like the path loss and the RMS delay spread. However, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…The work [148] introduces a beam-tracing method instead of the ray-tracing to reduce the number of path traces in the prediction. It is often reported that the predicted and measured PAS and PDP show differences [149]- [151], which in many cases are attributed to the lack of diffuse scattering in the ordinal raytracing [69].…”
Section: Site-specific Prediction Methodsmentioning
confidence: 99%
“…The work [148] introduces a beam-tracing method instead of the ray-tracing to reduce the number of path traces in the prediction. It is often reported that the predicted and measured PAS and PDP show differences [149]- [151], which in many cases are attributed to the lack of diffuse scattering in the ordinal raytracing [69].…”
Section: Site-specific Prediction Methodsmentioning
confidence: 99%
“…The relatively small mm-wave propagation environment allows easy and fast RT prediction, thus overcoming its traditional drawback: high computation time. Moreover, due to its accuracy and versatility RT can be used to derive simpler path-loss models [61] [62] or to directly perform multidimensional channel characterization, often in combination with measurements [34], [63]- [65]. Since RT models by definition simulate multipath propagation, they can be used to evaluate and/or compare the performance of MIMO solutions (e.g.…”
Section: A Deterministic and Semi-deterministic Modelsmentioning
confidence: 99%
“…This eliminates the huge cost of measurement campaigns [99], [159], [163], [164]. At mmWave frequencies, several studies involved the ray tracing model for predicting the propagation behaviour of the channel in diverse scenarios, as in [103], [142], [151], [160], [164]- [166]. Additionally, several treatise used the ray tracing model to extract and analyze the physical characteristics of the channel, as in [76], [99], [142], [162], [165], [167].…”
Section: The Millimeter Wave Channel Modelmentioning
confidence: 99%
“…The spatio-temporal characteristics of the 60 GHz channel were also studied in [14], [28], [66], [69], [120], [121], [125], [142], [166], [175], [206], where the model of the indoor 60 GHz channel is based on the TSV [67] and on the extended-SV [171], [172] channel models. The general double-directional wideband CIR is given by:…”
Section: As Ds θmentioning
confidence: 99%